Self-motivated Learning Analysis: Study of Comparative Learning in Students Study Program Guidance for Islamic Counseling of UIN Suska Riau and UIN Imam Bonjol - Suhaimi Suhaimi; Mifathuddin Mifathuddin; Nurwita Nurwita; M. Fahli Zatrahadi; Darmawati Darmawati; Istiqomah Istiqomah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study has the potential to contribute significantly to understanding motivation in both institutions through a better understanding of self-motivated learning among students of the Islamic Counseling Guidance Study Program. Previous studies have explored the concept of self-motivated learning, but there are still research gaps that require further investigation by conducting comparative studies in two institutions. The purpose of this study is to answer how self-motivated learning is for students in the two institutions in the Islamic counseling guidance study program. Research methods use descriptive and qualitative methods. Analysis of data using Nvivo software The sample in this study was 22 people, including 2 lecturers and 20 other students from Uin Imam Bonjol and Uin Sultan Syarif Kasim. The research findings indicate that there is a shared comprehension among high-achieving students originating from renowned colleges in West Sumatra and Riau. The choice of counselling advice majors typically stems from parental influence, input from school teachers, or familial considerations. When it comes to developing self-motivation in learning, several factors should be taken into consideration. These include having well-defined objectives, being in a supportive atmosphere, following structured learning strategies, utilising effective learning techniques, ensuring adequate rest, fostering internal drive, maintaining a balance between different aspects of life, and seeking social support.